2005
DOI: 10.1021/ja053983e
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and Regioselective Reaction of La@C82with Cyclopentadiene

Abstract: The reversible and regioselective reaction of La@C82 with cyclopentadiene was carried out. The activation and thermodynamic parameter of the retro-reaction was estimated from the Arrhenius plots of the rate constants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 27 publications
0
51
0
2
Order By: Relevance
“…[43] Those derivatives were analyzed by HPLC and mass spectrometry, but the regiochemistry of the bisadducts was not described. Also in the same year Akasaka, Nagase, and co-workers [46] reported the reversible and regioselective addition reaction of La@C 82 (C 2v ; 1 a) with cyclopentadiene (Cp, 9), whereby Cp was added in excess to a degassed solution of 1 a in toluene (Scheme 4). The reaction was monitored by EPR over two hours in the dark.…”
Section: [4+2] Cycloadditions: Diels-alder Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[43] Those derivatives were analyzed by HPLC and mass spectrometry, but the regiochemistry of the bisadducts was not described. Also in the same year Akasaka, Nagase, and co-workers [46] reported the reversible and regioselective addition reaction of La@C 82 (C 2v ; 1 a) with cyclopentadiene (Cp, 9), whereby Cp was added in excess to a degassed solution of 1 a in toluene (Scheme 4). The reaction was monitored by EPR over two hours in the dark.…”
Section: [4+2] Cycloadditions: Diels-alder Reactionsmentioning
confidence: 99%
“…Furthermore, the retroDiels-Alder reaction was obtained at 298 K in toluene, with an activation energy even lower than that of the retro reaction of C 60 Cp. [46] Dorn and co-workers took advantage of the higher reactivity of empty fullerenes and classical EMFs compared to metallic nitride EMFs towards Diels-Alder reactions for the purification of metallic nitride EMFs from the extracted fullerenes.…”
Section: [4+2] Cycloadditions: Diels-alder Reactionsmentioning
confidence: 99%
“…Metallofullerenes (MFs) have been used with many organic reactions including as: [1 + 2] cycloadditions, 33 [3+2] cycloadditions, 34,35 Prato reactions, 33,36,37 and Diels-Alder type cycloadditions. 34,38 Cui et al 38 documented the nature of an encapsulated metal cation for the regioselectivity and the reactivity in the Diels-Alder (DA) cycloaddition of cyclopentadiene (CpH) to M + @C 60 (M = Li, Na, K, Rb, and Cs) and Ca 2+ @C 60 by density functional theory in the gas phase and solvents. It was shown that metal cations could promote the reactions of CpH and C 60 because they decrease the activation barriers and make the reactions more exothermic and exergonic, or less endothermic and endergonic.…”
Section: Fullerene Derivatives: the Race To Characterizementioning
confidence: 99%
“…116 DielsAlder (DA) reaction of La@C 2v (9)-C 82 with cyclopentadiene (Cp) proceeded smoothly to afford a single product. 117 The high regioselectivity is noteworthy because 24 nonequivalent carbons and 19 nonequivalent 6,6-ring junctions are on the C 2v (9)-C 82 cage. However, the thermal instability of the product hampered the determination of the molecular structure.…”
Section: Sbclmentioning
confidence: 99%